1757a Future of work, and strategic research perspectives from the nordic occupational health research institutes. (24th April 2018) - Mattila-Wiro, Päivi; Husberg, Wiking; Vänskä, Anne; Tuomi, Timo; Sæmundsson, Eyjolfur; Samant, Yogindra; Bye, Sture; Winzor, Glen; Fallentin, Nils; Green, Peter; Stone, Nina; Falk, Magnus
Abstract : Introduction: Emerging risks, and constantly changing technologies which have an impact on the world of work require a continuously updated knowledgebase for policy makers and practitioners. The Nordic research institutes have a unique position in this effort where they attempt to provide strategic research inputs to the Future of Work initiative. Methods: Discussions in the group, Nordic research institutes inputs on strategic research perspectives looking in to the Future. Results: Perspectives Reports provides insights in to the strategic needs, with regard to Future of Work and occupational health. Discussion: The current perspectives report provided by the Nordic Future of Work Group, set up in 2016 as an initiative by the Director Generals of the Nordic Labour Inspectorates, has provided a basis upon which both the Nordic inspectorates and the Nordic institutes of occupational health have seen a need for building the knowledge base. The broad mandate of the group includes the potential for recommending areas of research and research activities, and may as well include both continuous research within existing areas as well as potential new areas of research. Recommendations expected to come together with the research strategies of the Nordic institutes of occupational health in each Nordic country. This presentation will provide some of the background for the strategic research perspectives from the Nordic countries aligned with the perspectives report and ongoing research on Future of Work.